Integrasi Transportasi Laut Berbasis Green Logistics Untuk Meningkatkan Nilai Tambah Pemasaran Produk Maritim - Karjono; Evyana Diah Kusumawati; Karmanis (Politeknik bumi Akpelni, 2025)
The transformation of maritime supply chains into more sustainable systems presents both a challenge and a strategic opportunity to enhance the competitiveness of marine products. This study explores the integration of sea transportation based on green logistics principles as an approach to generating added value in maritime product marketing. A qualitative case study method was employed, focusing on seafood processing and distribution businesses in the coastal areas of Central Java. Data were collected through in-depth interviews, field observations, and document analysis, and processed using triangulation techniques. The findings reveal that implementing green logistics in sea transportation significantly reduces logistics costs, minimizes carbon emissions, and accelerates product distribution to key markets. Moreover, the integration of information systems and renewable energy-based fleet management has proven to improve operational efficiency and enhance the sustainability image of the products in the eyes of consumers. The study underscores that collaboration among government bodies, industry players, and local communities is essential in developing environmentally friendly and economically valuable maritime transport systems. In conclusion, the green logistics strategy contributes not only to ecological benefits but also to the increased competitiveness of maritime products in both domestic and international markets.